A macromolecular trafficking complex composed of β2-adrenergic receptors, A-Kinase Anchoring Proteins and L-type calcium channels. (June 2013) - Flynn, Robyn; Altier, Christophe
Abstract Sympathetic modulation of cardiac L-type calcium channels is an important mechanism for regulating heart rate and cardiac contractility. At the molecular level, activation of β-adrenergic receptors (βAR) increases calcium influx into cardiac myocytes by activating protein kinase A (PKA), leading to subsequent phosphorylation of L-type calcium channels. In the case of the β2AR, this process is facilitated by the presence of A-Kinase Anchoring Proteins (AKAPs) that serve as scaffolding proteins for the L-type calcium channel and the β2AR complex. Our work has shown that, in addition to facilitating PKA phosphorylation of the channel, AKAPs also promote an increase in the Cav1.2 channel surface expression. Here we review the molecular mechanisms of β2AR/AKAP/L-type channel interactions and trafficking.